Tales Of Possession And Dispossession - Elsa Charléty (Sillages Critiques)
This paper looks at loss and grief in Edwidge Danticat’s novel Claire of the Sea Light (2013) through analyzing how absence is configured within the aesthetic of the novel. I show how the interwoven stories within the text form a narrative economy where people trade memories and emotions amongst themselves in order to cope with the void left by the departed. Drawing on Edwidge Danticat’s writings, as well as anthropological research in Haiti and theories of loss and grief in literary criticism, I show that Edwidge Danticat’s prose, while constantly negotiating the space between the collective and the individual, creates a language of exchange around the notion of absence. A polyphonic aesthetic of absence emerges from these exchanges to transform individual pain into collective memory.